Effect of Nb on the structural, optical and photocatalytic properties of Al-doped ZnO thin films fabricated by the sol-gel method. Issue 16 (November 2018) - Jafari, Hojat; Sadeghzadeh, Sadegh; Rabbani, Mahboubeh; Rahimi, Rahmatollah
Abstract: In this work, ZnO thin films doped with (1 atm%) Al and co-doped with (1–4 atm%) Niobium (Nb) (NAZO) have been prepared on soda lime glass substrates by using the sol-gel deposition method. Then the structural and optical properties and the photocatalytic activities of these Nb-Al co-doped ZnO films have been investigated. The presence of niobium as the second dopant changes the morphology of thin films and motivates the growth of nanorods. The density, diameter, and orientation of nanorods are affected and controlled by Nb content. The optical absorbance of all the examined samples increased with the increase of Nb content. The photocatalytic activities of the prepared thin films were also investigated by measuring the photodegradation of methylene blue as a pollutant. By achieving an 80% degradation of methylene blue dye, the best photocatalytic activity was displayed by the ZnO thin film doped with (1% at) Al and co-doped with (3% at) Nb (NAZO).